Y TXT N DRIVE? Predictors of texting while driving among a sample of Ontario youth and young adults. (January 2019) - Berenbaum, Erin; Harrington, Daniel; Keller-Olaman, Sue; Manson, Heather
Highlights: Descriptive norms were positively associated with sending text messages while driving. Risk perceptions were positively associated with reading text messages while driving. Perceived texting while driving (TWD) skills were positively associated with TWD behaviour. Abstract: Background: Distracted driving is of particular concern among young drivers. According to the 2012 National Highway Traffic Safety Administration (NHTSA) survey, the greatest proportion of distraction prone drivers is within the 16–19 and 20–24 age groups. One relatively new distraction is texting while driving behaviour (TWD). TWD increases the amount of time drivers spend looking away from the road, slows reaction times and increases the risk of collisions by two-fold. To deter this behaviour many distracted driving campaigns focus on highlighting the risks and dangers of distracted driving; however, evidence suggests that youth and young adults continue to engage in TWD despite awareness of the related risks. Previous studies have examined constructs from the theory of planned behaviour as predictors of TWD (e.g., attitudes, intentions). Understanding the full range of factors that may influence this behaviour can inform the development of evidence-based public awareness campaigns and related interventions. Purpose: The purpose of this paper was to examine predictors of TWD behaviour among youth and young adults. We examined constructs from the theory of planned behaviour in addition to the role played by perceived TWD driving skills, experience with collisions due to TWD, descriptive norms (i.e., an individual's beliefs about a behaviour that are gained as a result of observing the actions of others) and risk perceptions. Methods: An online survey was administered to 2001 Ontario youth and young adults examining potential predictors of TWD behaviour. Regression models were used to examine which key variables were associated with TWD (both reading and sending behaviour) among participants. Results: Overall, regression models had good predictability for reading and sending behaviours. Perceived TWD driving skills and ' almost getting in a collision due to TWD' were positively associated with TWD behaviour in the past week (both reading and sending behaviours). Descriptive norms were positively associated with sending text messages while driving in the past week, but were not significant for reading. In contrast, risk perceptions were positively associated with reading text messages in the past week but not sending. Discussion and conclusion: The results from this study highlight constructs that can be used to design interventions to deter young drivers from engaging in TWD. Interventions targeting perceived TWD driving skills and descriptive norms have the potential to be more effective than interventions emphasizing risk perceptions. Future studies are needed to better understand the relationships between these predictors and TWD behaviour among this population.